Insights into the Cyanobacterial Deg/HtrA Proteases - Cheregi, Otilia; Wagner, Raik; Funk, Christiane (Frontiers in Plant Science, 2016)
Proteins are the main machinery for all living processes in a cell; they provide structural elements, regulate biochemical reactions as enzymes, and are the interface to the outside as receptors and transporters. Like any other machinery proteins have to be assembled correctly and need maintenance after damage, e.g., caused by changes in environmental conditions, genetic mutations, and limitations in the availability of cofactors. Proteases and chaperones help in repair, assembly, and folding of damaged and misfolded protein complexes cost-effective, with low energy investment compared with neo-synthesis. Despite their importance for viability, the specific biological role of most proteases in vivo is largely unknown. Deg/HtrA proteases, a family of serine-type ATP-independent proteases, have been shown in higher plants to be involved in the degradation of the Photosystem II reaction center protein D1. The objective of this review is to highlight the structure and function of their cyanobacterial orthologs. Homology modeling was used to find specific features of the SynDeg/HtrA proteases of Synechocystis sp. PCC 6803. Based on the available data concerning their location and their physiological substrates we conclude that these Deg proteases not only have important housekeeping and chaperone functions within the cell, but also are needed for remodeling the cell exterior.